Capital and Labour in the Halifax Baking and Confectionery Industry During the' Last Half of the Nineteenth Century - Mckay, Ian (Labour / Le Travail, 1978)
The Halifax baking and confectionery industry was characterized by the uneasy coexistence of craft bakeries, manufactories, and one factory. A stratified system of production produced a stratified labour force, in which the journeymen bakers alone were able to organize a union. Their struggles reveal a cleavage between factory workers and other journeymen in the industry.